The Role of Mitochondrial H+-ATP Synthase in Cancer - Esparza-Moltó, Pau B.; Cuezva, José M. (Frontiers in Oncology, 2018)
Cancer cells reprogram energy metabolism by boosting aerobic glycolysis as a main pathway for the provision of metabolic energy and of precursors for anabolic purposes. Accordingly, the relative expression of the catalytic subunit of the mitochondrial H+-ATP synthase –the core hub of oxidative phosphorylation– is downregulated in human carcinomas when compared to its expression in normal tissues. Moreover, some prevalent carcinomas also upregulate the ATPase Inhibitory Factor 1 (IF1), which is the physiological inhibitor of the H+-ATP synthase. IF1 overexpression, both in cells in culture and in tissue-specific mouse models, is sufficient to reprogram energy metabolism to an enhanced glycolysis by limiting ATP production by the H+-ATP synthase. Furthermore, the IF1-mediated inhibition of the H+-ATP synthase promotes the production of mitochondrial ROS (mtROS). mtROS modulate signaling pathways favoring cellular proliferation and invasion, the activation of antioxidant defenses, resistance to cell death and modulation of the tissue immune response, favoring the acquisition of several cancer traits. Consistently, IF1 expression is an independent marker of cancer prognosis. In contrast, inhibition of the H+-ATP synthase by α-ketoglutarate and the oncometabolite 2-hydroxyglutarate, reduces mTOR signaling, suppresses cancer cell growth and contributes to lifespan extension in several model organisms. Hence, the H+-ATP synthase appears as a conserved hub in mitochondria-to-nucleus signaling controlling cell fate. Unraveling the molecular mechanisms responsible for IF1 upregulation in cancer and the signaling cascades that are modulated by the H+-ATP synthase are of utmost interest to decipher the metabolic and redox circuits contributing to cancer origin and progression.